Faktor Pengaruh Pertumbuhan Kredit Perbankan di Indonesia - Ganis Samodro Priyaninggar (Studi Akuntansi dan Keuangan Indonesia, 2017)
The aim of the research is credit growth of BUKU 4 in Indones reports from quarter 2 in 2005 until quarter 2 in 2015. This research gives contribution to Indonesian banks in forecasting the upcoming credit growth fund, Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), BI Rate, Gross Domestic Product (PDB) significantly affect the bank’s credit growth. While, inflation, Net Interest Margin (NIM), and exchange rates do not affect significantly. These results support the previous research done by Oktaviani and Pangestuti (2012) for third party fund and Capital Adequacy Ratio (CAR), Ivanovic (2015) for Non Performing Loan (NPL) and Rahayu (2013) for BI rates. Key words: third party fund (DPK), Gross Domestic Product (PDB) https://doi.org/10.21632/saki.1.1.25-42